IMPLEMENTASI KEBIJAKAN MANAJEMEN BERBASIS SEKOLAH (MBS) DAN BERBUDAYA MUTU DI SMA NEGERI 1 SIDOARJO - Sukesi Sukesi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
Along with the era of autonomy and democratic processes and the despair of decentralization, the development of quality requires participation and empowerment of all components of education and application of the concept of education as a system. Improving the quality of education within the framework of regional autonomy changes the direction and paradigm of governance that used to be a centralized pattern towards decentralized education. This research formulated the following issues: 1) how the quality of SBM planning in SMA Negeri 1 Sidoarjo, 2) how to develop organizational culture in the management of quality culture MBS in SMA Negeri 1 Sidoarjo, 3) how to socialize the quality culture in the management of education in SMA Negeri 1 Sidoarjo, 4) how to develop quality culture based on excellence in education management effort in SMA Negeri 1 Sidoarjo, and 5) how strategy to maintain MBS quality culture that has achieved excellence in SMA Negeri 1 Sidoarjo. The approach used in this research is qualitative. Sources of data in research are principals, waka, teachers. Techniques of data collection using observation methods, interviews and documentation. Data analysis technique is done through four activities, namely data collection, data reduction, data presentation, and conclusion. The results showed that: 1) SMA Negeri 1 Sidoarjo has arranged the management planning of MBS based on quality culture based on the value of values ​​and spirit developed. In the framework of planning and developing a school's quality culture, there are three steps that must be taken by the principal, namely: 1) Identification of spirit and values ​​as a source of school quality culture, .2) Continuous socialization of spirit and values ​​to all stakeholders, and 3) The principal always fosters the commitment of all stakeholders to uphold the spirit and values, 2) SMA Negeri 1 Sidoarjo seeks to develop SBM in the management of education based on quality culture. In this case the steps taken by the principal, namely: 1) Defined the development of a quality culture as an official policy of the school, 2) Routine socialization of values ​​to all stakeholders ,. And 3) The principal always fosters the commitment of all school members to uphold the values ​​that have been established together, 3) In the effort of socialization appear in the making of an SBM policy in SMA Negeri 1 Sidoarjo is (1) leads to improving the quality and effectiveness of the school, (2) involves all the citizens of the school so as to grow a sense of ownership because of accommodated inputs, and become (3) decisions through agreement and democratic, 4) SMA Negeri 1 Sidoarjo can be categorized superior, which has the characteristics: (1) have strong academic culture, (2) having a curriculum that is always relevant to the development of science and technology, (3) having a school community that always creates innovative ways to learn, (4) oriented to the development of quality and excellence, (5) ) learning process to develop student's potential, and (6) developing process of ability development and competence of student's communication and 5) In an effort to maintain as a superior school, the efforts undertaken in SMA Negeri 1 Sidoarjo include: (1) spirit and values ​​that have been done by superior schools, which serve as a reference or basis for the development of a superior quality school culture, 2) a form of quality culture that remains visible in: (a) school vision and mission, (b) organizational structure and description of school work.